Greek religion and cults in the Black Sea region goddesses in the Bosporan Kingdom from the Archaic period to the Byzantine era - Braund, David 1957- (Cambridge University Press, 2018)
This is the first integrated study of Greek religion and cults of the Black Sea region, centred upon the Bosporan Kingdom of its northern shores, but with connections and consequences for Greece and much of the Mediterranean world. David Braund explains the cohesive function of key goddesses (Aphrodite Ourania, Artemis Ephesia, Taurian Parthenos, Isis) as it develops from archaic colonization through Athenian imperialism, the Hellenistic world and the Roman Empire in the East down to the Byzantine era. There is a wealth of new and unfamiliar data on all these deities, with multiple consequences for other areas and cults, such as Diana at Aricia, Orthia in Sparta, Argos' irrigation from Egypt, Athens' Aphrodite Ourania and Artemis Tauropolos and more. Greek religion is shown as key to the internal workings of the Bosporan Kingdom, its sense of its landscape and origins and its shifting relationships with the rest of its world
Title from publisher's bibliographic system (viewed on 15 May 2018)
Aims, contexts, and connectivity -- Crimean Parthenos, Artemis Tauropolos, and human sacrifice -- Crimean Parthenos in Greece, Anatolia, and the Mediterranean world -- Artemis of Ephesus in the Bosporan Kingdom -- Bosporan Isis -- The Mistress of Apatouron: Aphrodite Ourania and the Bosporan Apatouria -- Artemis, Aphrodite and Demeter
Keywords: Goddesses, Greek; Antike; Griechisch; Göttin; Kult; Religion; Black Sea Region / Religion; Bosporanisches Reich; Schwarzmeer-Gebiet